Cyber Public Relations Herman Suherman dalam Kampanye Politik Bupati Cianjur 2020 - Faisal, Tengku; Nurani Muksin, Nani (Green Publisher Indonesia, 2024)
The development of communication technology allows the use of various media to convey messages. Cyber public Relations or so-called Cyber PR continues to have an impact when it enters the political context. The political campaign for the 2020 Cianjur regional head election also applies and feels the benefits of this cyber public relations. The condition of the Covid-19 pandemic has made digital media a means of campaigning for candidates, while for the public this digital media is used as a source of searching for information about the candidate. In addition, the candidates also use the internet as a means of socializing the program and its vision and mission. The purpose of this study was to determine the 3R concept, namely relations, reputation and relevance as a result of Herman Suherman's cyber public relations in the political campaign of the Cianjur regent of West Java in 2020. The method used in this study was a descriptive qualitative method. This study found that there are reputation, relevance and relationships related to the media, stake holders and their constituents. The results of this study show that first, relations as deputy regent and temporary regent had previously been formed at the media, community and stakeholder levels before and during the campaign period even after being elected as regent. Second, the reputation of Herman Suherman's cyber public relations results has begun to be used as a brand image formation before the campaign period until the campaign took place in various aspects including trustworthy, competency and historic both on the official website of Cianjur district and Instagram social media accounts. Third, relevance in the form of good innovations that were formed before the campaign period only needed a mitigation function to maintain the popularity and electability of candidates during the campaign period until they were elected as regent of Cianjur.